2012
DOI: 10.1371/journal.pone.0033880
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of a H3N2 Influenza Virus Containing a Deficient Neuraminidase Protein by a Hemagglutinin with a Low Receptor-Binding Affinity

Abstract: Influenza viruses possess at their surface two glycoproteins, the hemagglutinin and the neuraminidase, of which the antagonistic functions have to be well balanced for the virus to grow efficiently. Ferraris et al. isolated in 2003–2004 viruses lacking both a NA gene and protein (H3NA- viruses) (Ferraris O., 2006, Vaccine, 24(44–46):6656-9). In this study we showed that the hemagglutinins of two of the H3NA- viruses have reduced affinity for SAα2.6Gal receptors, between 49 and 128 times lower than that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…There is a considerable literature pertaining to the need for “balance” between HA and NA activities of influenza viruses, the idea being that if the receptor specificity changes with a change in host, then the NA specificity must follow. There are many examples of adjustments to activity levels [14; 21; 24; 30; 32; 34] but the specificity shows only modest changes [2; 15] and the NA always has higher activity on α2-3 than α2-6 sialylated glycans as summarized in Supplementary Table 1 of a recent review [1]. A more recent report [32] shows less activity with MUN substrate for recombinant NA of pdmH1N1 strain A/California/4/2009 (Kcat 3 sec −1 , Km 373 μM) than for older strains Japan/57 and Hong Kong/68 (Kcat 29 and 18 sec −1 , Km 79 and 20 μM, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…There is a considerable literature pertaining to the need for “balance” between HA and NA activities of influenza viruses, the idea being that if the receptor specificity changes with a change in host, then the NA specificity must follow. There are many examples of adjustments to activity levels [14; 21; 24; 30; 32; 34] but the specificity shows only modest changes [2; 15] and the NA always has higher activity on α2-3 than α2-6 sialylated glycans as summarized in Supplementary Table 1 of a recent review [1]. A more recent report [32] shows less activity with MUN substrate for recombinant NA of pdmH1N1 strain A/California/4/2009 (Kcat 3 sec −1 , Km 373 μM) than for older strains Japan/57 and Hong Kong/68 (Kcat 29 and 18 sec −1 , Km 79 and 20 μM, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In this vein, Blick et al reported that a zanamivir resistant virus incorporating an HA mutation that significantly impaired affinity, actually required the presence of the drug for viral growth, because returning functionality of the NA shifts the balance to overwhelming sialidase activity and HA cannot effectively complete the receptor binding and entry process [ 188 ]. Similarly, when NA is inherently defective, growth can be rescued by adaption of HA [ 189 , 190 , 191 , 192 , 193 ]. Baigent et al combined the study of HA glycosylation and NA stalk length, both characteristics found to change among transmission and adaptation, and illustrated a fine balance of the two modifications needed to sustain infection [ 67 ].…”
Section: Functional Balance Of Ha and Namentioning
confidence: 99%
“…There may also be other uncertainties, for example, host range restriction of influenza virus replication in CEFs. [38][39][40][41] In Vivo Anti-influenza Virus Activity in Specific Pathogen Free (SPF) Chicken…”
Section: Inhibition Of Influenza Neuraminidasesmentioning
confidence: 99%